A Mitochondrially Related Plastidial Transporter Regulates Photosynthesis in the Diatom Phaeodactylum tricornutum - Giustini, Cécile; Dal Bo, Davide; Storti, Mattia; Van Vlierberghe, Mick; Baurain, Denis; Cardol, Pierre; Zhang, Youjun; Fernie, Alisdair R.; Fitzpatrick, Duncan; Aro, Eva‐Mari; Allorent, Guillaume; Albanese, Pascal; et al. (Wiley, 2026)
Eukaryotic phototrophs depend on the activity of two engines (the plastid and the mitochondrion) to generate the energy required for cellular metabolism. Because of their overlapping functions, both activities must be closely coordinated. At the plastid level, optimisation occurs through alternative electron transport, the diversion of excess electrons from the linear transport chain and metabolic exchanges. A similar process takes place in the mitochondria, with documented evidence of energy and redox equivalents being exchanged between the two organelles. Organelle-organelle energy interactions at the physiological level are well established in diatoms, an ecologically significant member of phytoplankton. Yet the molecular components involved in this process remain largely unknown. Here, we identify a mitochondrial carrier family (MCF) transporter, MCFc, located at the plastid envelope of Phaeodactylum tricornutum, which seems to be widely distributed in complex algae. We then compare the performance of a wild-type and a mutant lacking MCFc. An analysis of spectroscopic and oxygen exchange data unveiled altered energetic interactions in the mutant, suggesting that MCFc plays a role in plastid-mitochondrion communication. In silico analysis of MCFc implies a similar substrate-specific model to that of ADP/ATP carriers, although distinct motif differences in MCFc indicate potential variations in its function, with possible substrates including arginine, aspartate/glutamate or citrate/isocitrate. Together, these findings support a role for mitochondrial energy metabolism in sustaining diatom photosynthesis, likely mediated by MCFc, though further investigation is needed to determine the precise mechanism.